The influence of conscientiousness and context on the emotional response during understanding - Jun, Jenny; Lazic, Milan; Woodruff, Earl (Frontiers in Psychology, 2025)
IntroductionIn this exploratory study, we use a logistic multilevel model to examine the interplay between personality, emotions, and understanding.MethodsThe impact of Conscientiousness, a Big Five Personality trait, on emotional responses during riddle-solving attempts was investigated in 101 participants, who each tackled 15 riddles remotely via Zoom. Video recordings were analyzed using iMotions with AFFDEX to identify the emotion type (positive, negative, and epistemic) experienced during the riddle-solving (understanding) process.ResultsThe study revealed significant effects of both positive and negative emotions on understanding scores. Upon examining cross-level interactions, the effect of trait Conscientiousness on the association between emotion type and understanding scores was not significant. Our random intercepts model appeared to provide the most satisfactory explanation for our exploratory findings. Further, the model demonstrated good discrimination ability, as evidenced by our area under the Receiver Operating Characteristic (ROC) curve.DiscussionOur results highlight the fundamental role of context, specifically the individual’s perceived value of a learning activity and the nature of their understanding—emergent or established—in shaping the emotions evoked during the process of understanding. For future endeavors, we recommend a concentrated focus on the complex interplay between personality, emotions, and understanding, especially when understanding is in its emergent phase and the task employed for measurement provokes emotional investment.